THE EFFECT OF DIRECT PAYMENTS ON FARM PERFORMANCE FOR THE CASE OF CEECs THROUGH STOCHASTIC FRONTIER ANALYSIS APPROACH - Anera MUSLIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Since the 1980s, agriculture in CEECs has been under continues pressure due to the changes in political, economic and institutional circumstances that have been closely linked to the transition process as well as to the process of integration into the European Union and openness to the world markets. The transition process led the agricultural sector to experience substantial reforms at both macroeconomic and at microeconomic levels. These changes were expected to increase the performance indicators of farms in these countries, however, they are still lower compared with the performance indicators of farms in developed countries. The aim of this paper was to calculate the technical efficiency scores of farms in CEECs though Stochastic Frontier Analysis approach and to measure the effect of direct payments on performance indicators. By using the FADN data for 11 CEE countries for the period 2004-2016, the results suggested that the average technical efficiency was 84%. Compared to Kosovo, this average technical efficiency score, as a proxy for farm performance, is very high. However, compared to more developed countries, these efficiency score can still increase by making more targeted agricultural policies. Direct payments are suggested to significantly and negatively affect the technical efficiency scores.